Public Transport Provision in Two Cities – Oxford and Odense - Holvad, Torben (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
In the last decade(s) significant changes in the regulatory structure of urban public transport have been implemented in a number of European countries including United Kingdom, Sweden, Germany and Denmark. Although, there are differences between the countries in terms of the details of the reforms general trends include some form of deregulation in order to enable entry to the public transport industry. In most cases deregulation has been linked to the introduction of competitive tendering procedures for the selection of the public transport service operators such that increased competition is mainly off the road rather than on the road. These trends are supported by EC initiatives; in particular the proposals for the revision of Regulation 91/1893 include provisions for competitive tendering for public transport services where contracts should be valid for a fixed term. This paper will provide a comparison of public transport provision in two cities, Odense and Oxford, in terms of organisational and regulatory frameworks used for bus service provision. A comparison of these cities is interesting because public transport is organised in significantly different ways – in Oxford; bus services are based on an open entry model, whereas bus services in Odense are provided by a public entity (Odense Bytrafik). In contrast to the rest of Great Britain usage of buses in Oxford has increased significantly since bus deregulation was implemented through the Transport Act 1985.